2020
DOI: 10.1186/s12885-020-07634-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior cancer history on the survival of patients with larynx cancer

Abstract: Background Patients with a prior history of cancer are commonly excluded from clinical trial. Increasing number of studies implied that a prior cancer did not adversely affect the clinical outcome among various types of cancer patients. However, the impact of prior cancer on survival of larynx cancer patients remains largely unknown. The aim of this study was to evaluate the prevalence of prior cancer and assess its impact on survival of patients diagnosed with larynx cancer. Methods Patients with larynx canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…In consequence, the detrimental effect of secondary PCa appears robust and generalizable. The observation of Zhu et al validates our hypothesis about the aggressiveness of primary cancer that may impact, as well as determine the natural history of treated secondary malignancies (24). The above findings, especially that with longer time interval between primary cancer and secondary PCa life expectancy approximates the life expectancy to primary PCa, should be considered treatment decision making, when secondary PCa patients are counseled.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In consequence, the detrimental effect of secondary PCa appears robust and generalizable. The observation of Zhu et al validates our hypothesis about the aggressiveness of primary cancer that may impact, as well as determine the natural history of treated secondary malignancies (24). The above findings, especially that with longer time interval between primary cancer and secondary PCa life expectancy approximates the life expectancy to primary PCa, should be considered treatment decision making, when secondary PCa patients are counseled.…”
Section: Discussionsupporting
confidence: 69%
“…Second, the nature of our data does not allow to define specific mortality time points to estimate Kaplan-Meier actuarial mortality rates. This limitation is shared with all previous publications focusing on secondary cancers, after specific primary cancers in large-scale databases (24)(25)(26). Limited stage and grade information was available for each of the 10 examined primary cancers and matching could not be performed for PSA and Gleason grade group without losing secondary PCa patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we guessed that there was no enrichment for a cancer type that may increase the risk of developing EC as an SPM. Similarly, Zhu et al [ 20 ] reported that the most common types of prior cancers in larynx cancer patients were from prostate, lung and bronchus, urinary bladder, and breast. Laccetti et al [ 21 ] found that prostate, gastrointestinal, breast, and other genitourinary were the most common types of prior cancer in locally advanced lung cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Instead, only OM was available. This limitation is shared with all previous publications focusing on secondary cancers after specific primary cancers in large‐scale databases 30–32 . Limited stage and grade information was available for each of the six examined primary cancer.…”
Section: Discussionmentioning
confidence: 99%